2010
DOI: 10.1016/j.ijcard.2008.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of CA125 in advanced heart failure patients

Abstract: Introduction: Serum levels of CA125 are often high in advanced heart failure (AHF) patients. Aim: To determine the predictive value of CA125 in forecasting the occurrence of death or cardiac transplantation in an AHF population. Methods: 88 AHF patients referred for heart transplantation were divided into 2 groups based on CA125 levels: normal (CA125 b 38 U/mL) and elevated (≥ 38 U/mL). Events (death or heart transplant) were monitored over a period of 13 ± 7 months after CA125 determination. Results: Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 16 publications
3
18
0
2
Order By: Relevance
“…In agreement with previous observations [1,2], Monteiro et al [3] reported that carbohydrate antigen 125 (CA125) was an independent predictor of increased mortality and heart transplantation in patients with acute heart failure (HF). The exact mechanism responsible of CA125 elevation in HF patients is not totally elucidated.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with previous observations [1,2], Monteiro et al [3] reported that carbohydrate antigen 125 (CA125) was an independent predictor of increased mortality and heart transplantation in patients with acute heart failure (HF). The exact mechanism responsible of CA125 elevation in HF patients is not totally elucidated.…”
supporting
confidence: 91%
“…Coronary stents pose a challenge in the perioperative period. Given the anecdotal evidence and case series suggesting that Drug Eluting Stents (DES) may be more vulnerable to thrombosis on discontinuation of antiplatelet agents (APT) than are bare-metal stents (BMS) [1][2][3][4], we sought to quantify this risk. We evaluated all patients who underwent noncardiac surgery (NCS) in a 3-year period.…”
mentioning
confidence: 99%
“…70,71 CA-125 levels are associated with the presence of symptoms and increased risk of adverse events and appears to have incremental value over BNP, the logistic EuroSCORE, and New York Heart Association Class. 72,73 CA-125 also correlates with echocardiographic measures of LV and atrial size and function, and appears not to be influenced by renal function, age, or body mass index.…”
Section: Cancer Antigen 125 (Ca-125)mentioning
confidence: 94%
“…CA125 is now recognised as a strong indicator of survival [75,76]. Filipiak et al [77] have also found that simultaneous measurement of BNP and CA125 gives the highest predictive ability for death risk in heart failure and showed that while a low left ventricular mass index or low eGFR have mortality odds ratios of 18 and 19 respectively, CA125 in combination with NT-proBNP had a mortality odds ratio of 493!…”
Section: Index Isovolumetric Relation Time and The Early To Late Mitmentioning
confidence: 99%